Islamic literature and sastera Islami: a conceptual comparison - Ahmad H.Osman, Rahmah (IIUM Press, 2006)
The term “Islamic literature” consists of two fundamental components, “Islamic” and “literature”. It is the questions surrounding these two components, which a major part of this article will address. The focus of this article is on the conceptual thinking underlying Islamic literature as a discourse in Malaysia and the Middle East. It investigates the criteria for classifying literature as Islamic from the perspective of Middle Eastern literary scholars such as Sayyid Qutb and Muhammad Qutb in the light of the Islamic world view. It then proceeds to define Islamic literature according to Middle Eastern and Malay scholars. It then examines these definitions according to the deduced criteria of what is Islamic Literature. It is found in both traditions that for literature to be deemed Islamic it has to conform to al tasawwur al Islãmi and it must not be at variance with Islamic values.